Associations Among Diffusion Tensor Image Along the Perivascular Space (DTI-ALPS), Enlarged Perivascular Space (ePVS), and Cognitive Functions in Asymptomatic Patients With Carotid Plaque - Liu, Hui; Yang, Shuai; He, Wei; Liu, Xiaojuan; Sun, Shanyi; Wang, Song; Wang, Yang; Zhou, Xiaoliang; Tang, Tao; Xia, Jian; Liu, Yunhai; Huang, Qing (Frontiers in Neurology, 2022)
Background & Aim: Carotid atherosclerosis (CAS) is a common pathogenesis of cerebrovascular disease closely related to stroke and silent cerebrovascular disease (SCD), while the insufficient brain perfusion mechanism cannot quite explain the mechanism. The purpose of this study was to utilize diffusion tensor image analysis along the perivascular space (DTI-ALPS) to evaluate glymphatic system activity and correlated DTI-ALPS with ePVS, CIMT, MMSE as well as serological indicator in individuals with carotid plaque. Methods: Routine MRI and diffusion tensor images scan of the brain, carotid ultrasound and blood examination were conducted on 74 individuals(52 carotid plaque subjects，22 non-carotid plaque subjects), whose demographic and clinical characteristics were also recorded. DTI-ALPS index between carotid plaque patients and normal controls were acquired and the correlations with other variables were analyzed. Results: The ALPS-index values in carotid plaque group was significantly lower compared to normal controls（2.12±0.39,1.95±0.28 respectively，p=0.034.ALP-index showed negatively correlated with BG-EPVS score（r=-0.242，p=0.038）while there is not significant difference in CSO-ePVS score. Further analysis showed there are more high-grade ePVS in BG compared carotid plaque group than in non-carotid plaque group（84.6% vs 40.9% p=0.001）. Conclusions: ALPS-index reflects glymphatic system of the brain, which is associated with early high-risk cerebrovascular diseases. There may be damage in the function of the glymphatic system and induce the expansion of the perivascular space in the basal ganglia in individuals with carotid plaque.